Closing the gap - Is type 2 diabetes awareness enough to prevent the growing epidemic?. Issue 3 (May 2019) - Cuschieri, Sarah; Grech, Stephan
Abstract: Background: Diabetes mellitus is a public health burden requiring a multi-sectorial approach including adequate population awareness to tackle this epidemic. The study was aimed to determine the level of diabetes awareness among a high-risk dysglycaemic population in relation to socio-demographic, lifestyle and family history of diabetes as well as to body mass index (BMI) and blood pressure measurements. Furthermore, the authors strived to explore any relationships between diabetes awareness and an oral glucose tolerance test dysglycaemia diagnosis. Method: Participants obtaining impaired fasting blood glucose in a representative health examination survey were invited to undergo an oral glucose tolerance test (OGTT). During the OGTT session, participants were invited to take part in a diabetes awareness questionnaire as well as have their weight, height and blood pressure measured. Association between awareness scores and different parameters (age, gender, education, residential district, smoking, alcohol habit, family history, BMI and blood pressure) were explored. Results: Being a female, ageing, non-smoker and having a family history of diabetes had a positive association with adequate diabetes awareness. Even though generally good awareness was present, the majority of the participants were obese, with an elevated blood pressure and obtained a dysglycaemic status post OGTT. Conclusion: Diabetes awareness solely does not appear to engage individuals in preventive initiatives. Behavioural changes are required but these are only established after the motivational action gap has been overcome. Empowering community diabetes mellitus screening programs targeting the environment, social gradients and cultural norms while engaging in preventive interventions are recommended.